Physical activity and health - Bouchard, Claude; Blair, Steven N.; Haskell, William L. (Human Kinetics, 2012)
Designed for final year students and graduates studying kinesiology, exercise science, physical education, public health, preventive medicine and human biology, this title looks at the health benefits associated with a physically active lifestyle and a moderate level of fitness versus the potential deleterious consequences of physical inactivity.